2011
DOI: 10.1063/1.3553395
|View full text |Cite
|
Sign up to set email alerts
|

Time resolved metal line profile by near-ultraviolet tunable diode laser absorption spectroscopy

Abstract: Pulsed systems are extensively used to produce active species such as atoms, radicals, excited states, etc. The tunable diode laser absorption spectroscopy (TD-LAS) is successfully used to quantify the density of absorbing species, but especially for stationary or slow changing systems. The time resolved-direct absorption profile (TR-DAP) measurement method by TD-LAS, with time resolution of μs is proposed here as an extension of the regular use of diode laser absorption spectroscopy. The spectral narrowness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…Then a low voltage is maintained between the high power pulses. Such an arrangement of an argon discharge with aluminum target was explored by Vitelaru et al 25 who found that the steady state metastable density between the high power pulses is up to 10% of the maximum metastable density in the pulse. The same order of magnitude was found independently by Britun et al, 14 however without pre-ionization.…”
Section: Phys Plasmas 22 113508 (2015)mentioning
confidence: 99%
“…Then a low voltage is maintained between the high power pulses. Such an arrangement of an argon discharge with aluminum target was explored by Vitelaru et al 25 who found that the steady state metastable density between the high power pulses is up to 10% of the maximum metastable density in the pulse. The same order of magnitude was found independently by Britun et al, 14 however without pre-ionization.…”
Section: Phys Plasmas 22 113508 (2015)mentioning
confidence: 99%
“…The TD-LAS technique is usually employed for stationary plasmas [30]or time averaged measurements in pulsed plasmas [31], but has been adapted in various ways to perform time resolved measurements [21,22,24]. The method proposed in this paper uses the diode laser in its regular scanning mode, at very low scanning frequency (less than 0.2 Hz).…”
Section: Principles Of Time Resolved Td-lasmentioning
confidence: 99%
“…An absorption spectroscopy technique, which directly performs time resolved measurements in the afterglow of a pulsed discharge, has recently been proposed in [21]. This technique uses diode lasers in their regular scanning regime, at frequencies around 1Hz, and the precise synchronization between the laser scan and plasma pulses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The planar magnetron used in experiments is operated with a 10 cm-diameter titanium cathode and run in dc and pulsed excitation regimes with argon as a working gas; a detailed description of the source and chamber is provided elsewhere [10]. The magnetic field is radial and is set using concentric permanent magnets (a cylindrical magnet at the cathode center and an annular magnet at the outer edge of the cathode^.…”
mentioning
confidence: 99%